A unified approach for thermoelastic constitutive modeling of composite structures. (1st September 2019) - Liu, Xin; Yu, Wenbin; Gasco, Federico; Goodsell, Johnathan
Abstract: Mechanics of structure genome (MSG) has been extended to provide a unified approach to predict the thermoelastic behaviors of composite structures. The variational statement of the MSG models has been modified to capture pointwise temperature distribution in composite structures. The effective coefficients of thermal expansions (CTEs) are predicted using the MSG solid model whose accuracy is validated using the three dimensional (3D) finite element analysis (FEA). Thermal induced stress resultants are derived based on the extended MSG plate and beam models, which are used to describe the thermoelastic behaviors of thin or slender structures. The traditional fiber reinforced laminates and complex woven composite structures subjected to distributed temperature loads are analyzed using the proposed method. The results, including both the structural responses and local 3D stress fields, are predicted and compared with the ones from direct numerical simulations (DNS) using 3D FEA. Highlights: A unified thermoelastic constitutive modeling approach is proposed for composite structures. Pointwise temperature loads are incorporated into the constitutive modeling. Thermal stress resultants are derived based on MSG to define shell and beam elements. Thermal-induced structural responses and local stress fields can be accurately predicted with a high efficiency. The proposed method is applicable for general composite structures (e.g. UD laminates and 3D woven composites).